P093 Performance of four diagnostic assays for detecting herpes simplex virus type 2 antibodies in middle east and north africa. (14th July 2019) - Dargham, Soha; Nasrallah, Gheyath; Sahara, Afifah; Elsidiq, Malaz; Abu-Raddad, Laith
Abstract : Background: Assessments of commercial assays in detecting herpes simplex virus type 2 (HSV-2) antibodies have shown variable sensitivity and specificity, and variation in performance by global population. We aimed to evaluate performance of four assays in detecting HSV-2 antibodies in a composite Middle Eastern and North African (MENA) population. The assays are two ELISA kits: HerpeSelect ® 2 ELISA IgG and Euroimmun Anti-HSV-2 (gG2) ELISA (IgG), and two immunoblot (IB)/Western blot (WB) assays: HerpeSelect ® 1 and 2 Immunoblot IgG and Euroimmun Anti-HSV-1/HSV-2 gG2 Euroline-WB (IgG/IgM). Methods: Blood specimens were drawn from blood donors between 2013–2016 in Doha, Qatar. Twenty specimens from ten nationalities (Egypt, Iran, Jordan, Lebanon, Pakistan, Palestine, Qatar, Sudan, Syria, and Yemen; total=200) were randomly selected and tested for HSV-2 antibodies. Results: In the six possible assay comparisons, Cohen's kappa statistics indicated fair to good agreement, ranging between 0.57 (95% CI 0.28–0.86) and 0.69 (95% CI 0.44–0.95). Meanwhile, positive percent agreement ranged between 50.0 (95% CI 18.7–81.3%) and 63.6% (95% CI 30.8–89.1%); negative percent agreement ranged between 97.8% (95% CI 94.4–99.4%) and 99.5% (95% CI 97.0–100.0%); and overall percent agreement ranged between 95.8% (95% CI 91.9–97.9%) and 97.5% (95% CI 94.2–98.9%). The two ELISA kits demonstrated comparable sensitivities and specificities ≥50% and >98%, respectively, with respect to the IB/WB assays. Conclusion: The study provided, for the first time, primary data on performance of these assays in diagnosing HSV-2 infection in MENA populations. Findings support comparable performance and utility of these assays, and demonstrate challenges in establishing seropositivity (versus seronegativity). Disclosure: No significant relationships.